2010
DOI: 10.1177/0885328209360933
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-component Fiber-reinforced PHEMA-based Hydrogel/HAPEXTM Device for Customized Intervertebral Disc Prosthesis

Abstract: Spinal disease due to intervertebral disc degeneration represents a serious medical problem which affects many people worldwide. Disc arthroplasty may be considered the future ''gold standard'' of back pain treatment, even if problems related to available disc prostheses are considered. Hence, the aim of the present study was to improve the artificial disc technology by proposing the engineering of a pilot-scale device production process for a total multi-component intervertebral disc prosthesis. The device is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 23 publications
0
96
0
Order By: Relevance
“…IVD degeneration represents a spinal disease. Even though discectomy and fusion are the two most common surgical approaches for treating a degenerated disc, they are far from ideal treatments since they alter the biomechanics of the spine [90,[94][95][96][97][98][99]. For this reason, the ideal solution to a degenerated disc would involve an artificial disc [90,91,94,[97][98][99][100].…”
Section: Intervertebral Disc: From Repair To Regenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…IVD degeneration represents a spinal disease. Even though discectomy and fusion are the two most common surgical approaches for treating a degenerated disc, they are far from ideal treatments since they alter the biomechanics of the spine [90,[94][95][96][97][98][99]. For this reason, the ideal solution to a degenerated disc would involve an artificial disc [90,91,94,[97][98][99][100].…”
Section: Intervertebral Disc: From Repair To Regenerationmentioning
confidence: 99%
“…It has been well reported that the intervertebral disc prostheses currently available on the market undergo failure mainly because of wear or mismatch between the mechanical proprieties of the implanted device and the natural tissue [99,101]. In addition, current disc prostheses basically consist of a polymeric core interposed between two metallic plates (i.e., LINK SB Charite and ProDisc) possessing standard sizes [99][100][101][102][103].…”
Section: Intervertebral Disc: From Repair To Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nano-hydroxyapatite (nHA), owing to its chemical similarity to the inorganic component of natural bone, has been widely used for bioactive coating of orthopaedic implants [12,13,[16][17][18]. To improve the integration ability of the implants with the nearby bone tissues, a number of different coating techniques have been employed for the preparation of nHA-coated implants, which includes solution-based techniques [4,19,20], ionic sputtering [21,22] and plasma spraying [23,24].…”
Section: Introductionmentioning
confidence: 99%